2014
DOI: 10.1007/978-3-319-13972-2_3
|View full text |Cite
|
Sign up to set email alerts
|

LINKS: Learning-Based Multi-source IntegratioN FrameworK for Segmentation of Infant Brain Images

Abstract: Segmentation of infant brain MR images is challenging due to insufficient image quality, severe partial volume effect, and ongoing maturation and myelination processes. In the first year of life, the image contrast between white and gray matters of the infant brain undergoes dramatic changes. In particular, the image contrast is inverted around 6-8 months of age, and the white and gray matter tissues are isointense in both T1-and T2-weighted MR images and thus exhibit the extremely low tissue contrast, which p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
41
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 27 publications
(41 citation statements)
references
References 63 publications
0
41
0
Order By: Relevance
“…It should be noted that similar work has been presented in Ref. 26, in which a sequence of random forest classifiers was used for infant brain segmentation. However, the spatial prior, which is important for segmentation, 23,24 was ignored in Ref.…”
Section: Introductionmentioning
confidence: 95%
See 2 more Smart Citations
“…It should be noted that similar work has been presented in Ref. 26, in which a sequence of random forest classifiers was used for infant brain segmentation. However, the spatial prior, which is important for segmentation, 23,24 was ignored in Ref.…”
Section: Introductionmentioning
confidence: 95%
“…Recently, random forest [22][23][24][25][26][27] has attracted rapidly growing interest. It is a nonparametric method that builds an ensemble model of decision trees from random subsets of features and the bagged samples of the training data and has achieved state-of-the-art performance in many imageprocessing problems.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This includes the development of specialised tools for tissue segmentation that address the difficulties in resolving tissue boundaries blurred through the presence of low resolution and partial volume. A variety of techniques have been proposed for tissue segmentation of the neonatal brain in recent years: unsupervised techniques (Gui et al, 2012), atlas fusion techniques (Weisenfeld and Warfield, 2009;Gousias et al, 2013;Kim et al, 2016), parametric techniques (Prastawa et al, 2005;Song et al, 2007;Xue et al, 2007;Shi et al, 2010;Cardoso et al, 2013;Makropoulos et al, 2012;Wang et al, 2012;Wu and Avants, 2012;Beare et al, 2016;Liu et al, 2016), classification techniques (Anbeek et al, 2008;Srhoj-Egekher et al, 2012;Chiţȃ et al, 2013;Wang et al, 2015;Sanroma et al, 2016;Moeskops et al, 2016) and deformable models (Wang et al, 2011;Dai et al, 2013;Wang et al, 2013Wang et al, , 2014. A review of neonatal segmentation methods can be found in Devi et al (2015); Makropoulos et al (2017).…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5] Thus, automatic labeling of brain MR images becomes a notable topic in the field of medical image analysis. Due to the burden of manual brain labeling, it is imperative to develop an automatic and reliable brain labeling method.…”
Section: Introductionmentioning
confidence: 99%